Mental strategies and the perception of effort : implications for the psychological training of marathon runners - Schomer, Helgo (Department of Psychology, 2024)
[missing pages 7-18] Several attempts have recently been made by psychologists to uncover the mystique that surrounds the superior athletes and their superior performance. Researchers wonder whether continuous participation in a specific sport induces both peak performance and certain mental strategies or whether the perchance or purposeful adoption of a cognitive strategy enhances performance (Cratty, 1983). In their effort to find a causal relationship, psychologists have endeavoured to understand the mental processes of athletes, speculating on how the quality or quantity of their thoughts might contribute to their excellent performance. Yet results have been clouded over by anecdotal reports and rather unsystematic accounts of subjective experiences and views. Tentative explorations into the mind of the marathoner are beginning to set the stage for the unravelling of this highly .complex and.fas~inating realm. This research project sets out to focus on the mental strategies of the marathoner and to discover their contribution to the marathoner's limit of performance.